The genus Milnesium (Tardigrada: Eutardigrada: Milnesiidae) in the Great Smoky Mountains National Park (North Carolina and Tennessee, USA), with the description of Milnesium bohleberi sp. nov. - Bartels, Paul J.; Nelson, Diane R.; Kaczmarek, Łukasz; Michalczyk, Łukasz (Zootaxa, 2014)
For many decades the genus Milnesium was thought to consist of a single, cosmopolitan species: Milnesium tardigradum Doyère, 1840. However, recently the genus has been re-evaluated, and numerous new species have been described. Currently, over twenty extant species and one fossil are recognised, and most appear to have very narrow geographic ranges. It is doubtful that M. tardigradum sensu stricto is truly cosmopolitan, but to evaluate this hypothesis, specimens previously identified as M. tardigradum must be re-examined using newly proposed taxonomic characters. As part of the All Taxa Biodiversity Inventory (ATBI) we collected Milnesium specimens from various locations in the Great Smoky Mountains National Park (GSMNP). Two Milnesium species have been evaluated, and one of them, Milnesium bohleberi sp. nov., is new to science. The new species is most similar to M. eurystomum but differs by shorter claws and a shorter, narrower, and more cylindrical buccal tube. The other Milnesium species, very rare in our collection, is morphologically indistinguishable from Milnesium granulatum Ramazzotti 1962, which was previously known only from Chile, Italy and Romania. Based on the recently revised description of M. tardigradum sensu stricto, this nominal species for the genus has not been found in the GSMNP samples.